Assessment of the Implementation of Psychological First Aid Training: Adaptation and Validation of Determinants of the Implementation Behavior Questionnaire - Rojas-Andrade, R (Taylor and Francis, 2024)
Objective: Psychological First Aid (PFA) is essential in emergencies and disasters. However, if incorrectly applicated, it can have negative consequences for the mental health of both those providing assistance and those receiving it. Therefore, it is important to have adequate tools to measure the implementation the quality of PFA training. The Determinants of Implementation Behavior Questionnaire was adapted and validated in a sample of PFA trainers in Chile. Methods: One hundred and one trainers completed the questionnaire translated into Spanish. The instrument was subjected to a process of item reduction to ensure its viability, the adjustment of the instrument s factorial structure to the theoretical frameworks used in the field was analyzed and its reliability was evaluated. Results: A scale with 18 items divided into 5 dimensions was obtained. The results indicated an acceptable fit to the theoretical model (χ2/gl = 1.106, CFI =.997, TLI =.996, RMSEA =.033). All dimensions showed good reliability (Ω =.668 -.793). Discussion: The instrument validly and reliably assesses behavioral determinants of implementation. An adapted, validated, short-form instrument will facilitate evaluations of the implementation of PFA training. © 2023 Informa UK Limited, trading as Taylor & Francis Group.